2020
DOI: 10.4314/tjpr.v19i4.28
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice of Lebanese community pharmacists with regard to self-management of low back pain

Abstract: Purpose: To determine the knowledge, attitude and reported practice of Lebanese community pharmacists who advise persons who present with low back pain.Methods: This was a multi-center cross-sectional study conducted in over 300 community pharmacies across Lebanon from December 2017 to May 2018. Pharmacists working at a community pharmacy were considered eligible, and those who volunteered to participate completed the questionnaire. The questionnaire was designed for self-completion by the pharmacist and inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Among descriptive cross-sectional studies, 48 studies out of 49 achieved good quality scoring and only one achieved fair quality scoring. Qualitative and mixedmethod studies all achieved good quality scoring (see Nigeria [36,40], China [37], Poland [38], Iran [39], Malaysia [44], Jamaica [41], Jordan [42], Pakistan [43] Intermediate care service 2 UK (Ireland) [66,67] Public health activities 2 Yemen [48], Nigeria [49] Cancer health promotion 1 Ghana [78] Breast cancer health promotion 6 Qatar [79], Iraq [84], Jordan [80], UAE [81], Palestine [82], Malaysia [83] Breast and bowel cancer screening 1 Australia [85] Drive-thru service 2 Jordan [22,88] Travel medicine services 1 Malaysia [73] Weight management services 2 UK [86], Malaysia [76] Nutrition counselling 1 Egypt [77] Mental health services 3 UK [55], Malaysia [56], Canada [57] Pain management 1 Lebanon [62] Smoking cessation 2 Malaysia [74], Jordan [75] professional practice 2 Malaysia [53], UAE [54] Oral health services 2 Malaysia [69], Lebanon [70] Minor Aliment services 1 Malaysia [51] Lifestyle assistance to cardiovascular disease 1 Malaysia [58] Osteoporosis risk assessment 1 Malaysia [61] Servic...…”
Section: Methodological Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Among descriptive cross-sectional studies, 48 studies out of 49 achieved good quality scoring and only one achieved fair quality scoring. Qualitative and mixedmethod studies all achieved good quality scoring (see Nigeria [36,40], China [37], Poland [38], Iran [39], Malaysia [44], Jamaica [41], Jordan [42], Pakistan [43] Intermediate care service 2 UK (Ireland) [66,67] Public health activities 2 Yemen [48], Nigeria [49] Cancer health promotion 1 Ghana [78] Breast cancer health promotion 6 Qatar [79], Iraq [84], Jordan [80], UAE [81], Palestine [82], Malaysia [83] Breast and bowel cancer screening 1 Australia [85] Drive-thru service 2 Jordan [22,88] Travel medicine services 1 Malaysia [73] Weight management services 2 UK [86], Malaysia [76] Nutrition counselling 1 Egypt [77] Mental health services 3 UK [55], Malaysia [56], Canada [57] Pain management 1 Lebanon [62] Smoking cessation 2 Malaysia [74], Jordan [75] professional practice 2 Malaysia [53], UAE [54] Oral health services 2 Malaysia [69], Lebanon [70] Minor Aliment services 1 Malaysia [51] Lifestyle assistance to cardiovascular disease 1 Malaysia [58] Osteoporosis risk assessment 1 Malaysia [61] Servic...…”
Section: Methodological Qualitymentioning
confidence: 99%
“…The included studies are presented in Additional file 1, which shows pharmacists' awareness, perceptions, or attitudes toward various extended pharmacy services and drive-thru service at community setting including: extended role services [35], pharmaceutical care services [36][37][38][39][40][41][42][43][44], over-the-counter pharmaceutical services [45,46], health promotion and health education [47], public health activities [48,49], value-added services [50], minor aliment services [51], medication reconciliation [52], professional services [53,54], services for people with mental disorders [55][56][57], lifestyle assistance services for people with cardiovascular diseases [58], anticoagulation management services [59], services for geriatrics [60], osteoporosis assessment screening [61], back pain management services [62], Human Papillomavirus (HPV) Vaccination Services [63], emergency contraception services [64], clinical services [65], intermediate care services [66,67], interactions with general practitioners [68], oral health services [69,70] [71,72], travel medicine services [73], smoking cessation counselling [74,<...…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study revealed that different factors are involved in the incidence of LBP in clinical workers especially some staffs who do heavy works like patients transferring in the hospital [5] . Several studies have shown the effectiveness of knowledge, attitude and behavior promotion based educational interventions on prevention of LBP [6][7] . Previous evidence reported that negative attitudes towards LBP preventive behaviors could leading to pain severity and disability.…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence reported that negative attitudes towards LBP preventive behaviors could leading to pain severity and disability. On other hands positive beliefs towards LBP preventive behaviors could promote healthy LBP preventive behaviors and prevent LBP [6] . As to our knowledge there is no study regarding the impact of educational program on knowledge, attitudes and To collect data a demographic questionnaire as well as a researcher -made questionnaire consisted of subscales of knowledge, attitude and behavior questions were used.…”
Section: Introductionmentioning
confidence: 99%